English Language Teacher Motivation in Sri Lankan Public Schools - Hettiarachchi,Sujeewa (2013 Academy Publisher, Finland, 2013)
Drawing on in-depth qualitative data from fifty-four surveys and five interviews, this study investigated aspects of motivation and demotivation among Sri Lankan English language teachers, The participants included a convenience sample of English teachers currently employed in public schools, The results of the study revealed that students themselves, the act of teaching students, and the prestigious social position for English teachers in Sri Lanka are main motivators for teachers. The main demotivators for the participants included limited facilities for teaching and learning in schools, inefficiency of school administration and zonal education offices, difficulties in obtaining teacher transfers, the discrepancy between the English curriculum and students' English proficiency, and the poor relationship between colleagues. Overall results of the study indicate that teacher demotivation is a significant issue in Sri Lankan public schools which needs the immediate attention of the country's education policy designers and management.
Keywords: motivation; demotivation; English teachers; public schools; Sri Lanka